(untitled) (Research, Society and Development, 2020)
Biophysics is an interdisciplinary science that makes up the curriculum of undergraduate courses in the biological and health areas. It is a fundamental discipline for understanding phenomena such as physiology. However, its interdisciplinary nature is responsible, in many cases, for causing difficulties in learning this discipline. Factors such as the lack of correlation between the different disciplines that compose it, superficial learning habits and the absence of more up-to-date theoretical and practical methodologies and materials are usually associated with the difficulty in learning biophysics. Therefore, this article aimed to present teaching-learning methods, in order to promote improvement in teaching biophysics. A narrative review was carried out based on the literature published between 2000 and 2018, available on academic portals such as SciELO, Google Scholar and Periódicos CAPES. The following keywords were used: Biophysics teaching, teaching-learning methods and difficulties in learning biophysics. It was possible to observe in the literature consulted, the use of non-traditional assessments as concept maps and Information and Communication Technologies (ICTs) as alternatives to assessment through written test in this discipline. The monitoring of students by a monitor and the realization of practical classes are also of great importance for teaching Biophysics. Thus, the topics covered in the study, allow a better understanding of the difficulties in learning biophysics, proposing solutions for teaching the discipline.